Brilliantia kiribatiensis, a new genus and species of Cladophorales (Chlorophyta) from the remote coral reefs of the Southern Line Islands, Pacific Ocean. Issue 2 (17th January 2022) - Leliaert, Frederik; Kelly, Emily L. A.; Janouškovec, Jan; Fox, Michael D.; Johnson, Maggie D.; Redfern, Farran M.; Eria, Taati; Haas, Andreas F.; Sala, Enric; Sandin, Stuart A.; Smith, Jennifer E.
Abstract : The marine green alga Brilliantia kiribatiensis gen. et sp. nov. is described from samples collected from the coral reefs of the Southern Line Islands, Republic of Kiribati, Pacific Ocean. Phylogenetic analysis of sequences of the large‐ and small‐subunit rDNA and the rDNA internal transcribed spacer region revealed that Brilliantia is a member of the Boodleaceae (Cladophorales), containing the genera Apjohnia, Boodlea, Cladophoropsis, Chamaedoris, Phyllodictyon, and Struvea . Within this clade it formed a distinct lineage, sister to Struvea elegans, but more distantly related to the bona fide Struvea species (including the type S. plumosa ). Brilliantia differs from the other genera by having a very simple architecture forming upright, unbranched, single‐celled filaments attached to the substratum by a rhizoidal mat. Cell division occurs by segregative cell division only at the onset of reproduction. Based on current sample collection, B. kiribatiensis seems to be largely restricted to the Southern Line Islands, although it was also observed on neighboring islands, including Orona Atoll in the Phoenix Islands of Kiribati, and the Rangiroa and Takapoto Atolls in the Tuamotus of French Polynesia. This discovery highlights the likeliness that there is still much biodiversity yet to be discovered from these remote and pristine reefs of the central Pacific.